TrkB overexpression in mice buffers against memory deficits and depression-like behavior but not all anxiety- and stress-related symptoms induced by developmental exposure to methylmercury - Karpova, Nina N.; Lindholm, Jesse Saku Olavi; Kulesskaya, Natalia; Onishchenko, Natalia; Vahter, Marie; Popova, Dina; Ceccatelli, Sandra; Castrén, Eero (Frontiers in Behavioral Neuroscience, 2014)
Developmental exposure to low dose of methylmercury (MeHg) has a long-lasting effect on memory and attention deficits in humans, as well as cognitive performance, depression-like behavior and the hippocampal levels of the brain-derived neurotrophic factor (Bdnf)in mice. The Bdnf receptor TrkB is a key player of Bdnf signaling. Using transgenic animals, here we analyzed the effect of the full-length TrkB overexpression (TK+) on behavior impairments induced by perinatal MeHg. TK overexpression in the MeHg-exposed mice enhanced generalized anxiety and cue memory in the fear conditioning test. Early exposure to MeHg induced deficits in reversal spatial memory in the Morris water maze test and depression-like behavior in the forced swim test in only wild-type mice but did not affect these parameters in TK+ mice. These changes were associated with TK+ effect on the increase in Bdnf 2, 3, 4 and 6 transcription in the hippocampus as well as with interaction of TK+ and MeHg factors for Bdnf 1, 9a and truncated TrkB.T1 transcripts in the prefrontal cortex. However, the MeHg-induced anxiety-like behavior in the elevated plus maze and open field tests was ameliorated by TK+ background only in the open field test. Moreover, TK overexpression in the MeHg mice did not prevent significant stress-induced weight loss during the period of adaptation to individual housing in metabolic cages. These TK genotype-independent changes were primarily accompanied by the MeHg-induced hippocampal deficits in the activity-dependent Bdnf 1, 4 and 9a variants, TrkB.T1, and transcripts for important antioxidant enzymes glyoxalases Glo1 and Glo2 and glutathione reductase Gsr. Our data suggest a role of full-length TrkB in buffering against memory deficits and depression-like behavior in the MeHg mice but propose the involvement of additional pathways, such as the antioxidant system or TrkB.T1 signaling, in stress- or anxiety-related responses induced by developmental MeHg exposure.